Pengaruh Penambahan Glukosa-Leusin, Glukosa-Threonin terhadap Aroma Cokelat setelah Penyangraian Mikrowave = Pie Effect of Glucose-Leucin, Glucose-Threonin Addition to the Chocolate Aroma Following Microwave Roasting - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Dried bulk cocoa was dehulled, disintegrated to get ground nib. The nib was alkalized, added with glucose-leucin or glucose-threonin. The addition of glucose-amino acids was adjusted to get ratio of 1:1